Perda ambígua em cuidadoras de crianças com autismo: ela existe? - Oliveira, Cristiane Camargo de (Universidade Federal de São Carlos, 2011)
The ambiguous loss is the uncertainty or lack of information about the whereabouts or condition of a loved one. The ambiguity freezes the mourning process and it prevents cognitions, blocking strategy of coping and making-decision process. According to this theory, it can be observed either at the loss in which there is lack of information about a loved one or in the conflicting perception of the family in which members are considered present or absent in the inner circle. Few studies evaluate ambiguous loss in families with autists. The present research aimed: 1.To identify and describe the possible expressions of current feelings of the ambiguous loss in caregivers of children with autism; 2. To verify which coping strategies are more common in these caregivers; 3. To relate possible expressions of ambiguous identity to the measurements of stress and depression in these caregivers, as well as to the degree of severity of the autism. Four caregivers of children with autism aged from six to eight years participated in this study. The caregivers were interviewed on several topics related to the ambiguous loss and they answered instruments about stress, depression, strategy of coping and autism severity of their children. The interview content and the scores of the instruments of the four participants were analyzed. Afterwards, the reports of ambiguous identity with the stress punctuations, depression and autism level were associated. Three children had mild to moderate level and one severe level. All these caregivers presented stress and depression levels, with the prevalence of the coping strategies of social Support, Resolution of problems and Positive Revaluation. After the analysis of the semi-structured interview of ambiguity, it was observed the existence of feelings related to the ambiguous loss in all of these caregivers, with reports on the six categories. Lack of clarity about their child´s diagnosis was prevalent. The results showed the relationship between the increase of the frequency of ambiguous identity with the stress results and the severity of the autism. Based on the identification of experiences of ambiguous loss in these families with autist children, this present research can provide to the professionals further better assistance and a comprehensive and complete supporting to such families.
Keywords: Perda ambígua; Autismo; Estresse; Depressão; Coping; Educação especial; Família; Cuidadores; Autismo; Psicologia.; Ambiguous loss; Autism; Stress; Depression; Coping; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL